2022
DOI: 10.33448/rsd-v11i14.36024
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the knowledge of Polypores (Agaricomycetes) in the Amazonian Forest, with 16 new records for the state of Pará, Brazil

Abstract: We present an inventory of polypore fungi (Basidiomycota; Hymenochaetales and Polyporales) with the aim of knowing the diversity of an area of 8 km2 of Brazilian Amazon rainforest, in the surroundings of HPP Sílvio Braga, in the west of Pará, where 91 species were collected (545 specimens), with 16 of these new records for the state of Pará, and 1 for America. These numbers tend to increase, given the projected occurrence of 118 species for the area. 87 species were considered occasional or rare, with only fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In this study, all species are registered for the first time in the municipalities of Bujaru and Tomé-Açu; four species are new records for the state of Pará, and two of them are new records for the Brazilian Amazonia. The Flora do Brasil database (2020) presented 43 species of Hymenochaetaceae registered for the Brazilian Amazonia and recent taxonomical studies, including this family, also expanded the knowledge of the distribution of the species (Soares et al 2014, Silva et al 2021, Couceiro et al 2022. However, the new records found demonstrated the importance of fungal inventories in different areas of the Amazonia, to understand the true diversity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, all species are registered for the first time in the municipalities of Bujaru and Tomé-Açu; four species are new records for the state of Pará, and two of them are new records for the Brazilian Amazonia. The Flora do Brasil database (2020) presented 43 species of Hymenochaetaceae registered for the Brazilian Amazonia and recent taxonomical studies, including this family, also expanded the knowledge of the distribution of the species (Soares et al 2014, Silva et al 2021, Couceiro et al 2022. However, the new records found demonstrated the importance of fungal inventories in different areas of the Amazonia, to understand the true diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Fuscoporia callimorpha showed the largest number of specimens (3) and the only one collected in more than one study area, sítio Kenichi (2 occurrences) and sítio Corrêa (1 occurrence), but no host preference was found. Studies on Fuscoporia callimorpha demonstrated that species could be classified as rare or occasional (Xavier et al 2018, Couceiro et al 2022. The great representation of Fuscoporia species in forest areas is cited by Pires & Gugliotta (2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation